2014
DOI: 10.2147/clep.s65331
|View full text |Cite
|
Sign up to set email alerts
|

Long-term mortality in patients with pulmonary and extrapulmonary tuberculosis: a Danish nationwide cohort study

Abstract: BackgroundLong-term mortality and causes of death in patients with pulmonary tuberculosis (PTB) and extrapulmonary tuberculosis (EPTB) are poorly documented. In this study, long-term mortality and causes of death in PTB and EPTB patients were compared with the background population and it was investigated whether mortality was associated with family-related risk factors.MethodsA nationwide cohort study was conducted including: all adult Danes notified with PTB or EPTB from 1977 to 2008 and alive 1 year after d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 35 publications
2
23
0
1
Order By: Relevance
“…It is possible that patients with TB-CXR and positive cultures may have a higher Mtb bacillary load and more disseminated lesions, which may increase the risk for death. A similar result has been described by Christensen et al in their study in which pulmonary TB patients had an almost two-fold increased long-term mortality than extrapulmonary TB patients [ 25 ]. Although both TB-CXR and cavitation on CXR were evaluated in the initial multivariate model, only TB-CXR was significant.…”
Section: Discussionsupporting
confidence: 87%
“…It is possible that patients with TB-CXR and positive cultures may have a higher Mtb bacillary load and more disseminated lesions, which may increase the risk for death. A similar result has been described by Christensen et al in their study in which pulmonary TB patients had an almost two-fold increased long-term mortality than extrapulmonary TB patients [ 25 ]. Although both TB-CXR and cavitation on CXR were evaluated in the initial multivariate model, only TB-CXR was significant.…”
Section: Discussionsupporting
confidence: 87%
“…In contrary to this, younger patients had higher mortality in Chenai, India [ 17 ]. Clinical factors like smear-positivity, poor treatment outcome, multidrug-resistant TB (MDR-TB), late treatment start, history of previous treatment and comorbidity increased the risk of TB death [ 15 , 17 , 21 – 23 ]. Other studies also reported that poor nutrition and behavioral factors like smoking, alcoholism and drug abuse increased the risk of death due to TB [ 17 , 21 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Christensen et al described a similar result where pulmonary TB patients have an almost two-fold increased long-term mortality than extrapulmonary TB patients. 25 With poor living conditions, it is also obvious that patients who were homeless or reported being residents of a long-term care facility had a high rate of mortality. Different than Jung and coworkers' study that reported a higher mortality rate in the foreign-born TB patients in the whole U.S., 26 our data showed a higher mortality rate in U.S.-born TB patients in Texas.…”
Section: Discussionmentioning
confidence: 99%